2023
DOI: 10.3390/ijms241914437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Analysis of the Complete Plastomes of Five Epidendrum (Epidendreae, Orchidaceae) Species

Zhuang Zhao,
Meng-Yao Zeng,
Yu-Wei Wu
et al.

Abstract: Epidendrum, one of the three largest genera of Orchidaceae, exhibits significant horticultural and ornamental value and serves as an important research model in conservation, ecology, and evolutionary biology. Given the ambiguous identification of germplasm and complex evolutionary relationships within the genus, the complete plastome of this genus (including five species) were firstly sequenced and assembled to explore their characterizations. The plastomes exhibited a typical quadripartite structure. The len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the amino acid frequency for leucine (Leu) was the highest, while the frequency for cysteine (Cys) was the lowest in the encoded amino acids of the T. complanatum chloroplast. Our results matched well with previous studies on codon preferences in the Orchidaceae [25,63]. These findings also suggest a high similarity in codon usage frequency in orchid plants, further demonstrating the high conservation of the T. complanatum chloroplast genome (Table S4).…”
Section: Codon Usage Frequency Analysis and Amino Acid Abundancesupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the amino acid frequency for leucine (Leu) was the highest, while the frequency for cysteine (Cys) was the lowest in the encoded amino acids of the T. complanatum chloroplast. Our results matched well with previous studies on codon preferences in the Orchidaceae [25,63]. These findings also suggest a high similarity in codon usage frequency in orchid plants, further demonstrating the high conservation of the T. complanatum chloroplast genome (Table S4).…”
Section: Codon Usage Frequency Analysis and Amino Acid Abundancesupporting
confidence: 91%
“…Similarly, for the genus Paraphalaenopsis, regions such as psbB, ccsA, trnK UUU , trnS GCU -trnG UCC , and rps16-trnQ UUG show substantial differences [47]. In the case of Epidendrum, areas like trnC GCA -petN, trnD GUC -trnY GUA , trnS GCU -trnG UCC , and rpl32-trnL UAG are known for their maximum differences [63]. Furthermore, regions like atpI-atpH, matK, psbA-trnH, and trnL-F are typically used as marker genes to detect the evolution relationships within Aeridinae [66].…”
Section: Divergent Hot Spot Analysismentioning
confidence: 99%
“…Additionally, the quantity of long repeats varies among different genera of orchids. For instance, Aerides has 49-65 long repeats [53], Trichoglottis has 33-46 [54], and Epidendrum has 25-38 [55]. We believe these results could serve as valuable molecular resources for DNA marker development.…”
Section: Polymorphic Loci For Molecular Markersmentioning
confidence: 81%
“…Within the smaller SC region, genes such as accD and clpP shared similarities with the LSC regions of other Orchidaceae plastomes; genes within the larger SC region, particularly the four rRNA genes, exhibited similarity to the IR regions of other Orchidaceae plastomes. Previous studies reported nucleotide diversity values (Pi) of 0.14 for five Epidendrum plastomes and 0.129 for seven Trichoglottis plastomes [26,27]. In the case of E. roseum, the high intraspecific plastome polymorphism is manifested by Pi values reaching up to 0.146.…”
Section: Discussionmentioning
confidence: 98%